Patient Appointment Application for Mawar Medical Centre Unit – Dialysis - Endra kumar Muthu kumar; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2021)
It’s quite distressing to have to wait a long period for dialysis therapy from the doctors. Especially during this Movement Control Order (MCO) period. To solve this issue, a Patient Appointment Application was developed for Mawar Medical Centre - Dialysis Unit. The dialysis unit is still using a manual method which means all the documents and reports are kept in a file and organized by the unit staff. Implementation of this traditional method had brought up a lot of problems to the dialysis unit as well as to the patients. Some of the major problems are loss of data such as patient report and patient details, absence of online appointment booking for the patient to book time slot conveniently and the final problem is failure to generate statistical report for audit purpose. Next for objective this project holds three objectives. The first is i) to design a Patient Appointment Application using the Android platform. The second is ii) to develop a Patient Appointment Application that can send a reminder to the patient by using apps notification as an alert for the coming appointment. iii) to test the function of the Patient Appointment Application to work without errors. The development of this project will instantly solve the problem faced by dialysis unit management. The physical design of this application is being constructed using mobile-based technology, which are Android Studio, Firebase database and Java language. The methodology used in developing this application system is Object-Oriented System Development (OOSD) which involves four phases which are Object-Oriented Requirement Analysis, Object-Oriented Design, Object Oriented Implementation and Object-Oriented Testing. To conclude, this application will increase staff efficiency and productivity also makes it easier for the management to maintain a record the patient.